Proposed Business Strategy for Online Travel Reservation “TRAVY” PT. ANGKASA PURA II (Persero) (The Indonesian Journal of Business Administration, 2019)
PT Angkasa Pura II (Persero) is a State-Owned Enterpises which is given the authority to manage 16 airports in Indonesia. PT Angkasa Pura II through the Project Business Airport Digital Business has developed  e-commerce portfolio by creating an Online Travel Reservation or Online Travel Agent (OTR/OTA) product with the brand name "Travy".  In the process of planning, Travy is expected to become the new revenue stream. After undergoing 7 months implementation in the internal and external of PT Angkasa Pura II (Persero), Travy has not reach the target. The achievement of revenue target from Travy approximately 0.02 % of the target. This is a challenge for Project Business Airport Digital Business Unit that need to overcome and find ways to reach the target of revenue. The strategy is optimizing the corporate cooperation with PT Angkasa Pura II (Persero) group and other State owned- Enterprises and optimizing last minute ticket sales to accommodate the needs of passengers at airports. All of these process are carried out online by utilizing the Travy web application.In the process of implementation, Travy is expected to reach maximum revenue and were implemented at all subsidiaries of PT Angkasa Pura II (Persero) and other State- Owned Enterprise. The sales of Last-Minute Ticket will be installed as the default page on free internet service computer and Pop-Up Ads on Wi-Fi at all airports. Digital Lounge and Information Center at each airport will be used as a physical promotion asset for Travy, assisted by Customer service officer of PT Angkasa Pura II (Persero).Keywords:  New Revenue Stream, Online Travel Reservation/Online Travel Agent  (OTR/OTA), Marketing Strategy